Pressure recording analytical method and bioreactance for stroke volume index monitoring during pediatric cardiac surgery. Issue 2 (3rd February 2014) - Garisto, Cristiana; Favia, Isabella; Ricci, Zaccaria; Romagnoli, Stefano; Haiberger, Roberta; Polito, Angelo; Cogo, Paola; Hammer, Greg
Summary Background It is currently uncertain which hemodynamic monitoring device reliably measures stroke volume and tracks cardiac output changes in pediatric cardiac surgery patients. Objective To evaluate the difference between stroke volume index (SVI) measured by pressure recording analytical method (PRAM) and bioreactance and their ability to track changes after a therapeutic intervention. Methods A single‐center prospective observational cohort study in children undergoing cardiac surgery with cardiopulmonary bypass (CPB) was conducted. Twenty children below 20 kg with median (interquartile range) weight of 5.3 kg (4.1–7.8) and age of 6 months (3–20) were enrolled. Data were collected after anesthesia induction, at the end of CPB, before fluid administration and after fluid administration. Overall, median‐IQR PRAM SVI values (23 ml·m−2, 19–27) were significantly higher than bioreactance SVI (15 ml·m−2, 12–25, P = 0.0001). Correlation (r2) between the two methods was 0.15 (P = 0.0003). The mean difference between the measurements (bias) was 5.7 ml·m−2 with a standard deviation of 9.6 (95% limits of agreement ranged from −13 to 24 ml·m−2). Percentage error was 91.7%. Baseline SVI appeared to be similar, but PRAM SVI was systematically greater than bioreactance thereafter, with the highest gap after the fluid loading phase: 13 (12–18) ml·m−2 vs. 23 (19–25) ml·m−2, respectively, P = 0.0013. A multivariable regression model showed that a significant independent inverse correlation with patients' body weight predicted the CI difference between the two methods after fluid challenge (β coefficient −0.12, P = 0.013). Conclusions Pressure recording analytical method and bioreactance provided similar SVI estimation at stable hemodynamic conditions, while bioreactance SVI values appeared significantly lower than PRAM at the end of CPB and after fluid replacement.